1998
DOI: 10.1098/rspb.1998.0328
|View full text |Cite
|
Sign up to set email alerts
|

Task–specific impairments and enhancements induced by magnetic stimulation of human visual area V5

Abstract: Transcranial magnetic stimulation (TMS) can be used to simulate the e¡ects of highly circumscribed brain damage permanently present in some neuropsychological patients, by reversibly disrupting the normal functioning of the cortical area to which it is applied. By using TMS we attempted to recreate de¢cits similar to those reported in a motion-blind patient and to assess the speci¢city of de¢cits when TMS is applied over human area V5. We used six visual search tasks and showed that subjects were impaired in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 54 publications
13
112
1
1
Order By: Relevance
“…The time window (i.e., 60 -75 ms) of these effects is in line with previous studies revealing visual suppression by occipital TMS (Amassian et al, 1989), and is traditionally believed to correspond to the peak of the first volley of feedforward input in visual cortex (Martinez et al, 1999). Although transient disruption of brain function predominates in TMS research, there are also reports of functional improvements (Seyal et al, 1995;Walsh et al, 1998;Hilgetag et al, 2001;Paus, 2002, 2003;Kobayashi et al, 2004;Thut et al, 2005), similar to the RT facilitation we observed. Several studies further showed that stimulation of a given area can induce opposing (disruptive or facilitative) effects depending on task or behavioral context (Walsh et al, 1998;Paus, 2002, 2003).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The time window (i.e., 60 -75 ms) of these effects is in line with previous studies revealing visual suppression by occipital TMS (Amassian et al, 1989), and is traditionally believed to correspond to the peak of the first volley of feedforward input in visual cortex (Martinez et al, 1999). Although transient disruption of brain function predominates in TMS research, there are also reports of functional improvements (Seyal et al, 1995;Walsh et al, 1998;Hilgetag et al, 2001;Paus, 2002, 2003;Kobayashi et al, 2004;Thut et al, 2005), similar to the RT facilitation we observed. Several studies further showed that stimulation of a given area can induce opposing (disruptive or facilitative) effects depending on task or behavioral context (Walsh et al, 1998;Paus, 2002, 2003).…”
Section: Discussionsupporting
confidence: 75%
“…Although transient disruption of brain function predominates in TMS research, there are also reports of functional improvements (Seyal et al, 1995;Walsh et al, 1998;Hilgetag et al, 2001;Paus, 2002, 2003;Kobayashi et al, 2004;Thut et al, 2005), similar to the RT facilitation we observed. Several studies further showed that stimulation of a given area can induce opposing (disruptive or facilitative) effects depending on task or behavioral context (Walsh et al, 1998;Paus, 2002, 2003). The mechanisms invoked to explain beneficial TMS-effects are a disinhibition of unstimulated brain areas whose function are normally suppressed by the TMS target site (Seyal et al, 1995;Walsh et al, 1998) or a neural priming effect caused by TMS before a critical period Paus, 2002, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…The effects of on-line TMS, as used here, can be thought of as transiently introducing neural "noise" into the area stimulated (for review, see Walsh and Cowey, 2000;Walsh and PascualLeone, 2003). Many TMS studies adopting this interference approach have created a variety of "virtual lesions"; that is, behavioral changes mimicking those produced by lesions involving the same region [suppression of visual detection (Amassian et al, 1989), visual extinction (Pascual-Leone et al, 1994), prolongation of visual search (Ashbridge et al, 1997), akinetopsia (Walsh et al, 1998), aspects of spatial neglect (Fierro et al, 2000), or acalculia (Gobel et al, 2001)], thereby allowing tests of functional localization. Note that TMS differs from other types of neural stimulation [e.g., with implanted electrodes (Moore and Armstrong, 2003)] in many respects but can nevertheless similarly modulate a given region transiently to allow inferences about its function.…”
Section: Methodsmentioning
confidence: 99%
“…Motion perception in particular has proven to be very amenable to study using TMS (Beckers and Hömberg, 1992;Hotson et al, 1994;Beckers and Zeki, 1995;Anand et al, 1998;Walsh et al, 1998;Cowey et al, 2006;Laycock et al, 2007). However, thus far, only one study has specifically examined the effects of TMS to human area V5/MTϩ on the perception of speed (Matthews et al, 2001) and demonstrated that the application of TMS to the lateral occipital cortex can impair performance on speed discrimination tasks.…”
Section: Introductionmentioning
confidence: 99%